Vaccination with Plasmodium vivax Duffy-binding protein inhibits parasite growth during controlled human malaria infection - Hou, M; Barrett, JR; Themistocleous, Y; Rawlinson, TA; Diouf, A; Martinez, FJ; Nielsen, CM; Lias, AM; King, LDW; Edwards, NJ; Greenwood, NM; Kingham, L; et al. (American Association for the Advancement of Science, 2023)
There are no licensed vaccines against Plasmodium vivax. We conducted two Phase I/IIa clinical trials to assess two vaccines targeting P. vivax Duffy-binding protein region II (PvDBPII). Recombinant viral vaccines using chimpanzee adenovirus 63 (ChAd63) and modified vaccinia virus Ankara (MVA) vectors, as well as a protein and adjuvant formulation (PvDBPII/Matrix-M) were tested in both a standard and delayed dosing regimen. Volunteers underwent controlled human malaria infection (CHMI) following their last vaccination, alongside unvaccinated controls. Efficacy was assessed by comparison of parasite multiplication rate in blood. PvDBPII/Matrix-M, given in a delayed dosing regimen, elicited the highest antibody responses and reduced the mean parasite multiplication rate following CHMI by 51% (n=6) compared to unvaccinated controls (n=13), whereas no other vaccine or regimen impacted parasite growth. Both viral-vectored and protein vaccines were well tolerated and elicited expected, short lived adverse events. Together, these results support further clinical evaluation of the PvDBPII/Matrix-M P. vivax vaccine.